A STUDENT MODEL AND LEARNING ALGORITHM FOR THE EXPERT TUTORING SYSTEM OF POLISH GRAMMAR - Kostikov М.П.; Samsonov, B.B. (Journal of Information Technologies in Education (ITE), 2015)
When creating computer-assisted language learning software, it is necessary to use the potential of information technology in controlling the learning process fully. Modern intelligent tutoring systems help to make this process adaptive and personalized thanks to modeling the domain and students’ knowledge. The aim of the paper is to investigate possibilities for applying these methods in teaching Polish grammar in Ukraine taking into account its specifics. The article is concerned with the approaches of using student models in modern intelligent tutoring systems in order to provide personalized learning. A structure of the student model and a general working algorithm of the expert tutoring system of Polish grammar have been developed.The modeling of knowing and forgetting particular learning elements within the probabilistic (stochastic) model has been studied, as well as the prognostication of future probabilities of students’ knowledge, taking into account their individual forgetting rates. The objective function of instruction quality with allowance for frequency of grammar rules within a certain amount of words being learned and their connections to another rules has been formulated. The problem of generating the next learning step taking into account the need for mastering previous, connected rules has been studied, as well as determining the optimal time period between the lessons depending on the current knowledge level.